Human Activities Increase the Nitrogen in Surface Water on the Eastern Loess Plateau - Yuxian Hu; Ke Zhang; Yuan Li; Yanan Sun; Hongyan Li; Gaiqiang Yang (Geofluids)
Human activities have greatly accelerated the input of nitrogen into waters, resulting in water quality degradation. Facing the water crisis of nitrogen pollution, the state of surface water in arid areas needs close attention. Although numerous studies have indicated that waters’ nitrogen is often impacted by land use covers, the correlation between the two remains obscure. This paper explored the spatial relationship between anthropogenic activity and waters’ nitrogen on the eastern Loess Plateau, based on the Geographic Information System (GIS) spatial analysis using land use covers. There were 3 human land use types and 2 nitrogen indices used to assess the rivers’ state at the watershed scale. The results showed that rivers’ nitrogen was closely associated with human land use covers. Nitrogen pollution was most serious in urban areas. This study provided new evidence for the relationship between anthropogenic activities and river ecology. The findings may be helpful for policymakers to make strategic decisions of water resource management and land use planning in arid areas.